Malaysian corporate credibility based on the Sarawak native's perception - Rowena, Cliffton. (UNIMAS, 2009)
Corporate credibility is one issue that firms should address when assessing the effectiveness of their international or cross-cultural marketing efforts. Credibility measurement scales developed in the Western world often do not translate well to Asian contexts due to the difference of culture, belief and language. Therefore, this research addresses the issue of western-based scales of corporate credibility used in an Asian context by looking at the Sarawak Native’s perception of Malaysian Corporate Credibility. Besides, the result of this research can be used by the corporation in Malaysia to do the company self assessment in order to enhance their knowledge in understanding the market needs in Malaysia.